Investigating Push and Pull Factors Shaping the Travel Motivations of Young Indonesian Tourists to Vietnam: A Quantitative Approach - Latifah, Annisa Husnul; Shielline, Patricia; Erwen, Ivana Valencia (Yayasan Ilomata, 2024)
This study investigates the motivations driving young Indonesian travelers, particularly Millennials and Generation Z, to choose Vietnam as a travel destination. The research addresses a key gap in the literature by exploring the travel motivation using push and pull motivational factors. Using a quantitative approach, the study employed a self-administered questionnaire, distributed both online and offline to 144 young Indonesian travelers. The gathered data were analyzed using factor analysis to reduce the 39 push and pull motivational factors into a new set of underlying factors. Informal interviews and observation were also performed to support the analysis. The findings indicate that push motivation (internal psychological motivations), comprises of social achievement, learning motivation, stress relief, and social bonding were found to be four underlying push factors that motivate young Indonesian travelers to visit Vietnam. Meanwhile, travel standards, affordability, tourist amenities, cultural experiences, and natural landscapes appeared to be the pull factors. This finding serves as one of initial efforts to examine young Indonesian traveler’s behavior as the main target market for Vietnam Tourism. The study's implications also suggest that this study could provide a basis for Indonesian government to develop a more effective marketing strategies aimed at making local destinations more appealing to this segment compared to overseas options such as Vietnam. Furthermore, it is advisable for future research to study the characteristics of other generational groups as this could reveal significant differences compared to the younger generation.